Pengaruh Model Pembelajaran Snowball Throwing terhadap Kemampuan Mengidentifikasi Unsur Intrinsik Teks Drama Siswa Kelas VIII SMP Negeri O Mangunharjo - Melia Melia; M. Syahrun Effendi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2019)
The purpose of this study was to determine whether there is a significant influence on the use of the snowball throwing learning model on the ability to identify the intrinsic elements of drama texts of class VII students of SMP Negeri O Mangunharjo. The research method used a pure experimental method with a control group pre-test-post-test design. The population in this study were all students of Class VIII of SMP Negeri O Mangunharjo, amounting to 148 students. Two classes were taken as a sample using simple random sampling technique, namely class VIII C totaling 30 students as the experimental class and class VIII B totaling 30 students as the control class. Data collection techniques use test techniques in the form of essay tests. This data analysis technique is carried out using the "t" test. The results of the study showed that there was a significant effect of the snowball throwing learning model on the ability to identify the intrinsic elements of drama texts of class VIII students of SMP Negeri O Mangunharjo. This is evidenced by the results of tcount = 2.73 greater ttable = 2.00 at the significance level of 5% then Ho is rejected and Ha accepted.